Enabling the Individual: Simmel, Dewey and “The Need for a Philosophy of Education” - Koenig, Heike (Simmel Studies)

(untitled) (Georg Simmel Gesellschaft, 2019)
The essay brings together Georg Simmel’s and John Dewey’s reflections on the issues of education against the background of their diagnosis of a crisis in modern culture. In speaking of a “tragedy of culture” (Simmel) or, respectively, of a “tragedy of the lost individual” (Dewey) both thinkers stress the challenge the individual faces in constituting itself as a unity within a highly differentiated culture. I will show that both Simmel’s as well as Dewey’s considerations refer to the urgency of understanding individuality not as something static and fixed but as a coherent manner of interacting with continuously transforming conditions. This is an insight which emerges from Simmel’s “philosophy of life” as well as from Dewey’s “philosophy of experience” and it urges modern education to focus on enabling the individual’s “self-control” and “self-direction” within its own life and experience process.